ISOLASI DAN IDENTIFIKASI JENIS JAMUR PADA UBI KAYU (Manihot esculenta Crants.) DALAM PROSES PEMBUATAN UBI KAYU HITAM SECARA TRADISIONAL OLEH MASYARAKAT BANDA - Smith, Alwi; Hursepuny, Agnes (Biopendix: Jurnal Biologi, Pendidikan dan Terapan, 2015)
Background: One of the roles fungi also in the manufacture of cassava black is one of the food products in addition to the public Banda, cassava black produced by cassava (Manihot esculenta Crants.) The levels of HCN (Hydrogen Cyanide) high through a process of soaking and fermentation drying, assisted by a fungus that is capable of binding the HCN. Methods: The process of making cassava samples conducted in Banda black. Isolation and identification of fungi carried on laboratory Pattimura University Faculty of Teacher Training and Education Science Biology Study Program Ambon. Results: from isolation in cassava (Manihot esculenta Crantz) in the process of making cassava traditional black communities Banda fungal isolates obtained 5 with 3 different genera is Rhizopus, Aspergillus, and Penicillium. Based on observations of macroscopic and microscopic morphology isolat1 belonging to the genus Rhizopus, isolat2, isolat3, isolat4 belonging to the genus Aspergillus and isolat5 belonging to the genus Penicillium. Results of macroscopic observation while hanging in the manufacturing process cassava spread of colonies of black mold growing cassava which dominates in the genus Rhizopus and Aspergillus genus. Conclusion: Based on research results isolation and identification of fungi that grow on cassava (Mahinot esculenta Crantz) in the process of making cassava traditionally black community can Banda in 5 isolates identified are included in 3 different genera is Rhizopus, Aspergillius, and penicillium.